The role and policy of new media platforms in developing professional ethical responsibility in the Kurdistan Region. A filed study. - Azad Abdulazez Mohammed (Zanco Journal of Humanity Sciences)
The purpose of this research is to determine the measures and guidelines presented by new media platforms to their users when they encounter problems, and the researcher wishes to highlight how familiar Kurdish journalists are with the policies of new media platforms and themselves in the Professional Ethical Responsibility. They will track it down.